The Summer I Robbed a Bank - O'Doherty, David (UK, 2021)
There's a feeling of relief that comes just after you've robbed a bank... I want to write it all down, to figure our how the quickest kid in his class, the worst worrier and the scardiest scardey-cat became a bank robber. Rex's parents have just split up and, to make matters worse, he has to spend his summer holiday on a remote and rainy Irish island - with nothing but sheep for company. The only upside: his strange and brilliant uncle, Derm. The Rex discovers Uncle Derm is about to execute his most hare-brained plan yet. And he needs Rex's help...
Keywords: Adventure; Juvenile Fiction